Cost and affordability of healthy diets in Vietnam - Duong TT Van; Anna W Herforth; Huong T Trinh; Binh TT Dao; Ha TP Do; Elise F Talsma; Edith JM Feskens (Cambridge University Press, 2024)
Abstract Objectives: To estimate the cost and affordability of healthy diets recommended by the 2016-2020 Vietnamese food-based dietary guidelines (FBDG). Design: Cross-sectional analysis. The Cost of a Healthy Diet (CoHD) indicator was used to estimate the lowest cost of healthy diets and compare the cost differences by food group, region and seasonality. The affordability of healthy diets was measured by further comparing the CoHD to food expenditures and incomes. Setting: Food prices of 176 food items from January 2016 to December 2020 were derived using data from monthly Consumer Price Index databases nationally and regionally. Participants: Food expenditures and incomes of participants from three latest Vietnam Household Living Standard Surveys were used. Results: The average CoHD between 2016 and 2020 in Vietnam was 3·08 international dollars using 2017 Purchasing Power Parity (24 070 Vietnamese Dongs). The nutrient-rich food groups, including protein-rich foods, vegetables, fruits and dairy, comprised approximately 80 % of the total CoHD in all regions, with dairy accounting for the largest proportion. Between 2016 and 2020, the cheapest form of a healthy diet was affordable for all high-income and upper-middle-income households but unaffordable for approximately 70 % of low-income households, where adherence to the Vietnamese FBDG can cost up to 70 % of their income. Conclusions: Interventions in local food systems must be implemented to reduce the cost of nutrient-rich foods to support the attainment of healthier diets in the Vietnamese population, especially for low-income households.